PENERAPAN METODE JARINGAN SYARAF TIRUAN BACKPROPAGATION DALAM PENGENALAN POLA AKSARA HANACARAKA - Winardi, Sugeng; Hamzah, Hamzah (Jurnal Teknologi Informasi RESPATI, 2014)
Heritage and cultural property in the State of Indonesia very much . Various cultures spread across the country both dance culture , tribe , language and so forth . Script Hanacaraka including one of the nation's cultural heritage , particularly amongst today's Java island endangered if no rescue .Using Backpropagation Neural Network method can be used to perform pattern recognition Hanacaraka script handwriting . As one method of back propagation neural network is widely used and proven reliable enough for character recognition and handwriting or for other image recognition . By applying the backpropagation method to recognize handwritten characters Hanaraka pattern , then from several different handwriting samples , is expected to be obtained results are quite high recognition accuracy . Application to the analysis of handwriting recognition Hanacaraka script was developed with C # software .The results of this study are also expected to be able to help preserve the character Hanacaraka as one of Indonesia 's cultural heritage by learning how to write the script Hanacaraka correctly .Â Keywords :Â  Hanacaraka Alphabeth , Neural Networks , Backpropagation